Neuroprotective, Anticancer and Antimicrobial Activities of Azo-Schiff Base Ligand and Its Metal Complexes - Sarwade, Kirti N.; Sakhare, Kuldeep B.; Sakhare, Mahadeo A.; Thakur, Shailendrasingh V. (Karagandy University of the name of academician E.A. Buketov, 2025)
The synthesis of metal complexes of Mn(II), Co(II), Ni(II), Cu(II) Zn(II) and VO(II) from azo-Schiff base ligand was carried out by the condensation reaction of (E)-5-chloro-2-hydroxy-3-((3-nitrophenyl)diazenyl) benzaldehyde and 2-amino-4-nitrophenol. The structure of the synthesized azo-Schiff base ligand was con firmed by 1H-NMR spectra, mass spectra, FT-IR spectra. After confirmation of the azo-Schiff base ligand, metal complexes of Mn(II), Co(II), Ni(II), Cu(II), Zn(II) and VO(II) were synthesized using metal salts. These synthesized metal complexes were characterized by FT-IR spectra, elemental analysis, electronic spec tra, thermal analysis, X-ray powder diffraction, molar conductivity etc. In biological studies, the neuroprotec tive and anticancer activities of azo-Schiff base ligand and metal complexes were investigated by methylthia zole tetrazolium (MTT) assay on SHSY-5Y Neuroblastoma Cell line and MCF-7 human breast cancer cell line using Tacrine (TAC) and 5-Flourouracil (5-FU) as reference standard drugs, respectively. Also, antimi crobial potential was screened against two gram-positive (Staphylococcus aureus and Bacillus subtilis), two gram-negative (Klebsiella pneumonia and Pseudomonas aeruginosa) bacteria and three fungi (Penicillium chrysogenum, Tricoderma viride, and Aspergillus niger). Based on all the data obtained, it was concluded that metal complexes exhibit higher biological activity than ligands based on the azo-Schiff base.
Keywords: azo-Schiff base ligand; coordination compounds; metal complexes; azomethine; biological activi ty; neuroprotective; anticancer; antimicrobial